Peranan Pemerintah dalam Pengembangan Wayang Orang Panggung - Dhanang Respati Puguh; Mahendra Pudji Utama (Jurnal Sejarah Citra Lekha, 2018)
This article aims to discuss the role of the government in developing Wayang Orang Panggung especially in the Sriwedari community in Surakarta, Ngesti Pandowo in Semarang, and Bharata in Jakarta. This article based on the historical method. Since the beginning of Indonesian independence, the government carried out its function as a protector to maintain the existence of Wayang Orang Panggung, by improving the management of the performing arts, establishing the performance building, providing funding assistance, giving opportunities to perform at the state capital, and involving the artists of Wayang Orang in cultural missions. However, the government tended to be partial and more often conducted as a momentary response that must be addressed immediately because of it impossible to solve the community itself. Changes happened due to economic globalization and political dynamics in Indonesia that can threaten the existence of wayang orang and various forms of traditional arts. It raised hopes that the government could take the more fundamental role as patron-arts. In carrying out this function, the government requires a formulation on cultural policy as a basis for establishing the direction and strategy for the development and strengthening Wayang Orang Panggung and various forms of local culture, within the framework of national culture. The legal needed to carry out, UU RI No. 17 of 2017 about the Cultural Advancement, and Presidential Regulation No. 65 of 2018 concerning the Procedures for the Principles of Regional Culture and Cultural Strategies.